2018
DOI: 10.1007/s10384-018-0617-2
|View full text |Cite|
|
Sign up to set email alerts
|

Causes, background, and characteristics of binocular diplopia in the elderly

Abstract: About half of the elderly patients with binocular diplopia exhibited vertical deviation. In addition, binocular diplopia was often caused by orbital pulley disorders. It is the first epidemiological study focusing on orbital pulley disorders diagnosed on the basis of MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…Kawai et al suggested that binocular diplopia was often caused by orbital pulley disorders in elderly patients. 13 In our study, we did not group the causes of diplopia by age, but when we evaluated the causes for all ages together, age-related esotropia was the third most common cause (8.6%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Kawai et al suggested that binocular diplopia was often caused by orbital pulley disorders in elderly patients. 13 In our study, we did not group the causes of diplopia by age, but when we evaluated the causes for all ages together, age-related esotropia was the third most common cause (8.6%).…”
Section: Discussionmentioning
confidence: 94%
“…With age, lateral rectus-superior rectus band gets thinner and lateral rectus muscle displaces inferiorly. 13 Fusional range decreases with normal aging process and this condition also causes age related esotropia. Therefore, age related pulley abnormalities and decrease in fusional range should be considered in the presence of a new onset strabismus and diplopia in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Double vision is an extremely disabling symptom that can affect the quality of daily life of patients. Kawai et al investigated the clinical characteristics of patients aged ≥60 years who complained of binocular diplopia and found that the most common type of strabismus was esotropia due to orbital pulley disorder (9). They classified the causes of strabismus according to the type of deviation and demonstrated that orbital pulley disorder was the main reason for esodeviation, whereas it was convergence insufficiency for exodeviation, fourth nerve palsy for vertical deviation, and orbital pulley disorder and fourth nerve palsy in an equal frequency for combined deviation (9).…”
Section: Discussionmentioning
confidence: 99%
“…Kawai et al investigated the clinical characteristics of patients aged ≥60 years who complained of binocular diplopia and found that the most common type of strabismus was esotropia due to orbital pulley disorder (9). They classified the causes of strabismus according to the type of deviation and demonstrated that orbital pulley disorder was the main reason for esodeviation, whereas it was convergence insufficiency for exodeviation, fourth nerve palsy for vertical deviation, and orbital pulley disorder and fourth nerve palsy in an equal frequency for combined deviation (9). In the present study, there was one patient with sagging eye syndrome caused by the abnormalities of the extraocular muscle bands, which are primarily induced by the aging process (10).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of adult-onset strabismus is reported as 54/100,000 cases, peaking in the 8th decade of life. The most frequent forms of strabismus with diplopia are paralytic forms (44.2 %), convergence insufficiency (15.7 %), small-angle hypertropia (13.1 %) and distance esotropia (10.6 %) [1,2].…”
Section: Introductionmentioning
confidence: 99%